2007
DOI: 10.1093/ietcom/e90-b.9.2513
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Access Point Selection Architecture for Wireless LANs

Abstract: Wireless LANs have been widely deployed, and multiple access points (APs) will be much more likely to be available there for STAs, which can roam from one AP to another by some rule. We here focus on an efficient and fair way to use the wireless access resources provided by multiple APs. In particular, our major concern is to develop a decentralized way to enable each of STAs to select an appropriate one of available APs independently. A straightforward way is to select an AP with strongest signal, which will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 10 publications
0
49
0
Order By: Relevance
“…The problem of unbalanced AP load under RSSI based association was discussed in [2]. In [3,4], new metrics were studied to select a unicast AP instead of signal strength. Packet error rate and number of users were used in [3].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…The problem of unbalanced AP load under RSSI based association was discussed in [2]. In [3,4], new metrics were studied to select a unicast AP instead of signal strength. Packet error rate and number of users were used in [3].…”
Section: Related Workmentioning
confidence: 99%
“…In [3,4], new metrics were studied to select a unicast AP instead of signal strength. Packet error rate and number of users were used in [3]. The authors showed deployability and robustness of their AP selection architecture.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…To solve this problem, various AP selection methods [6]- [13] have been proposed and evaluated. In particular, [13] proposed an AP selection method based on cooperative movement of a new joining user and demonstrated that it improves system throughput (User-Only-Mobility Method: UOMM).…”
mentioning
confidence: 99%